STRATEGIC MANAGEMENT OF EDUCATION TO ENHANCE ENVIRONMENTAL-ORIENTED COMPETITIVENESS - Juni Iswanto; Amiartuti Kusmaningtyas; Murgianto Murgianto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2019)
This research is motivated by the strategy carried out by the board including collaborating / collaborating with alumni to promote their alma mater in new prospective students in their neighborhoods and workplaces can improve competitiveness by building a superior scientific culture of printing students as qualified quality learners tough facing the challenges of the times. This research uses a qualitative approach. Data collection techniques are in-depth interviews, observation, Focus Group Discussion, documentation. Data analysis techniques are data reduction, data presentation, and drawing conclusions / verification. From the results of this study, the researchers concluded that: Competitive strategies are carried out by: a) greater demand for good communication with the head and foundation for the advancement of madrasas, increasing education staff and infrastructure, b) Offers by preparing and managing students well, combining the curriculum of the Ministry of religion curriculum and the Salafiyah curriculum. c) Marketing by combining learning of the Ministry of religion curriculum and the Salafiyah curriculum, costs allocated according to the budget, alumni are real life brochures and through websites and competitions lined up, and access to madrasas is very easy and extends locations. Based on internal and external analysis above in a stable growth strategy condition which means that the situation is favorable because boarding schools have opportunities and strengths, boarding schools can take full advantage of opportunities so as to be able to implement strategies that support aggressive growth policies. Keywords: Strategic Management, Competitiveness